2019
DOI: 10.1002/mc.23091
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A‐SIN3A drives retinoic acid‐induced neuroblastoma differentiation by transcriptional repression of TERT

Abstract: Aggressive, high‐risk neuroblastoma (NB) exhibits an immature differentiation state, profound epigenetic dysregulation and high telomerase activity. It has been suggested that aggressive NB may be treatable by inducing differentiation whereas therapeutic targeting of telomerase is under investigation for multiple cancer types. While epigenetic regulation of the telomerase reverse transcriptase (TERT) promoter has been described in high‐risk NB, the exact molecular mechanisms are still not completely understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Promoter occupancy studies showed that ARID1A through SIN3A suppressed the expression of TERT, thus resulting in increased differentiation of NB cells. Patient data showed an inverse correlation between ARID1A and TERT expression, indicating a putative tumor suppressor role for ARID1A in NB [194].…”
Section: Chromatin Remodeling In Neuroblastoma By Atrx and Arid1a/1bmentioning
confidence: 94%
“…Promoter occupancy studies showed that ARID1A through SIN3A suppressed the expression of TERT, thus resulting in increased differentiation of NB cells. Patient data showed an inverse correlation between ARID1A and TERT expression, indicating a putative tumor suppressor role for ARID1A in NB [194].…”
Section: Chromatin Remodeling In Neuroblastoma By Atrx and Arid1a/1bmentioning
confidence: 94%
“…Each sample was scored and evaluated separately by 2 oncology pathologists. Immuno-scoring was used as per our previous study 12 to analyze both staining intensities and the proportion of anti‐COL11A1 (#HPA052246, Sigma‐Aldrich) and anti-Vimentin (SAB4503083, Sigma‐Aldrich) positive cells. Staining intensity was scored as 1 (weak), 2 (moderate), or 3 (strong).…”
Section: Methodsmentioning
confidence: 99%
“…NB samples were obtained from our NB cohort 12 in which clinical, biological and survival data has been collected for 5 years. 13 This study was approved by the Ethics Institutional Review Board of the University of Medicine and Pharmacy in Ho Chi Minh City, Vietnam (N0.UMP-2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the endometrial epithelium, we have previously shown that ARID1A normally promotes epithelial identity by repressing the expression of mesenchymal and invasion genes, at least in part through promoter-proximal and distal chromatin interactions that affect transcriptional activity (Reske et al, 2020; Wilson et al, 2020; Wilson et al, 2019). Other reports have demonstrated that ARID1A and SWI/SNF can function as a repressor, often through interactions with repressive machinery (Bui et al, 2019; Chandler et al, 2013; Rafati et al, 2011; Van Rechem, Boulay, & Leprince, 2009). Although nucleosome structure and histone post-translational modifications are suspected mechanisms, it remains poorly understood how SWI/SNF governs the epigenome.…”
Section: Introductionmentioning
confidence: 99%